2014
DOI: 10.5194/amt-7-2227-2014
|View full text |Cite
|
Sign up to set email alerts
|

Droplet activation of wet particles: development of the Wet CCN approach

Abstract: Abstract.Relationships between critical supersaturation required for activation and particle dry diameter have been the primary means for experimentally characterizing cloud condensation nuclei (CCN) activity; however, use of the dry diameter inherently limits the application to cases where the dry diameter can be used to accurately estimate solute volume. This study challenges the requirement and proposes a new experimental approach, Wet CCN, for studying CCN activity without the need for a drying step. The n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Ng et al ( 2010) compiled the measured O : C data from different environments and concluded that ambient organic aerosols mainly consist of oxygenated organic material (OOA) and hydrocarbon-like organic material (HOA) at most sites. HOA, which arises from vehicle emissions, is the least oxidized, with an average O : C value of less than 0.2 (Ng et al, 2010;Xu et al, 2015Xu et al, , 2016Cao et al, 2019;Li et al, 2020). Hence, with the inclusion of HOA in ambient aerosols, the average O : C value of the bulk organic is less than 1, being generally lower than our laboratory-generated aerosols.…”
Section: κ Vs O : C Ratiomentioning
confidence: 59%
See 1 more Smart Citation
“…Ng et al ( 2010) compiled the measured O : C data from different environments and concluded that ambient organic aerosols mainly consist of oxygenated organic material (OOA) and hydrocarbon-like organic material (HOA) at most sites. HOA, which arises from vehicle emissions, is the least oxidized, with an average O : C value of less than 0.2 (Ng et al, 2010;Xu et al, 2015Xu et al, , 2016Cao et al, 2019;Li et al, 2020). Hence, with the inclusion of HOA in ambient aerosols, the average O : C value of the bulk organic is less than 1, being generally lower than our laboratory-generated aerosols.…”
Section: κ Vs O : C Ratiomentioning
confidence: 59%
“…This phenomena complicates the accurate estimation of the actual water amount absorbed by the particles due to their intrinsic hygroscopicity. In a recent study by Nakao et al (2014), in order to avoid the influence from particle restructuring upon wetting, they sized wet particles without drying after generation and studied their droplet activation using a wet CCN. This approach might be easier to attempt, offering an unique solution for the current problems created by particle restructuring during the hydration processes.…”
Section: Amino Acidsmentioning
confidence: 99%
“…The thermal gradient in the CCN instrument is larger for larger supersaturation, and thus the decrease in κ with increasing supersaturation might be also due to volatilization . Volatilization experiments that measure aerosol diameter changes at ambient , or chilled temperatures or with liquid water to inhibit evaporation ,, could probe this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…We note that according to model calculations by Petters and Kreidenweis 49 , sulphuric acid has a CCN-relevant κ CCN of ~0.9; however, that κ CCN value is applicable only to aqueous sulphuric acid particles of relatively large dry diameter (> ~300 nm), as shown in Fig. S2 Dry generated iodine oxide has a κ CCN of 0.54 52 , which is close to the κ value of a particle consisting of a 36/64 -mixture (by volume) of rather hygroscopic organics (say, κ CCN = 0.25) and sulphuric acid (κ CCN ≈ 0.7), so that without any surface tension effects the iodine oxide will not provide the activation of the particle. In fact, if the dry particle contains 30 % (by volume) sulphuric acid, 30 % of the rather hygroscopic organic matter, and 40 % of substance X, the effective κ value of X needs to be as high as 1.5 for a 41 nm particle to activate at a supersaturation of 0.5 % (again, without any surface tension lowering effects and in this example for a rather high organic hygroscopicity).…”
Section: Ccn Closure and Sensitivity Analysismentioning
confidence: 92%